Diurnal Cycles of Meltwater Percolation, Refreezing, and Drainage in the Supraglacial Snowpack of Haig Glacier, Canadian Rocky Mountains - Samimi, Samira; Marshall, Shawn J. (Frontiers in Earth Science, 2017)
Meltwater refreezing and storage in the supraglacial snowpack can reduce and delay meltwater runoff from glaciers. These are well-established processes in polar environments, but the importance of meltwater refreezing and the efficiency of meltwater drainage are uncertain on temperate alpine glaciers. To examine these processes and quantify their importance on a mid-latitude mountain glacier, we measured the temperature and meltwater content in the upper 50 cm of the supraglacial snowpack of Haig Glacier in the Canadian Rocky Mountains. Thermistors and TDR probes were installed at 10-cm intervals at two sites in the glacier accumulation area from May to September, 2015. A Denoth meter was used to make point measurements for comparison with the TDR inferences of snowpack dielectric properties. These data are supplemented by automatic weather station data, used to calculate surface melt rates and drive a model of subsurface temperature, refreezing, and drainage. We observed a strong diurnal cycle in snow water content throughout the summer melt season, but subsurface refreezing was only significant in May; after this, overnight refreezing was restricted to a thin surface layer of the snowpack. Overnight decreases in water content after May are associated with meltwater percolation and drainage. There was negligible meltwater retention in the snow on a daily basis, but the refrozen water does represent an ‘energy sink’, with 10-15% of the available melt energy diverted to recycled rather than new meltwater. This reduces the total meltwater runoff from the site, even though no meltwater is retained in the system.